Two new species of Pyrocoelia Gorham (Coleoptera: Lampyridae) from Southwest China - Zhu, Chengqi; Xu, Xiaodong; Zhen, Ying (Zootaxa, 2022)
Two new species of the genus Pyrocoelia Gorham, 1880, Pyrocoelia cenwanglaoensis sp. nov. and P. rubrothorax sp. nov. were described from Mt. Cenwanglaoshan of Guangxi, Southwest China. Pyrocoelia cenwanglaoensis is morphologically similar to P. pectoralis Olivier, 1883 and P. amplissima Olivier, 1886, while Pyrocoelia rubrothorax resembles P. praetexta Olivier, 1911 and P. sanguiniventer Olivier, 1911 respectively, but these species can be distinguished based on external morphological characters and male genitalia. The diagnostic features of the two new species are described and illustrated based on morphological features. Phylogenetic reconstruction using cox1 barcoding sequences confirms the two new species belong to genus Pyrocoelia. We further summarized the distribution of accepted Pyrocoelia species currently known in China.